Pembelajaran Fisika Dengan Menggunakan Model Inkuiri Terbimbing Untuk Meningkatkan Keterampilan Proses Sains Siswa - Putri Rizqi Ramadhanti; Budi Jatmiko (Student Scientific Creativity Journal, 2023)
This study aims to determine the increase in students’ science prosess skills using the guided inquiry learning model. This research uses a literature review research method. A total of 4 articles were obtained to be used as data which was then analyzed. Data analysis uses 3 stages, organize (choose the type of journal that is in line with the research), synthensize (read and summarize journals), identify (draw conclusions from each journal). From the available data, it is known that using the guided inquiry learning model can improve students' science process skills in physics subjects.